Solve the following systems of equations:
√2x – √3y = 0
√3x − √8y = 0
Answers
Answered by
0
Answer:
ye hai kya ......
.....
Attachments:
![](https://hi-static.z-dn.net/files/d08/35d0960112c5f8c289923a076e70ec8d.jpg)
Answered by
2
x = 0 and y = 0
Step-by-step explanation:
Given: √2x – √3y = 0 -------------(1)
√3x − √8y = 0 -------------(2)
From equation 2, we get y = √3x/√8
Substituting this in equation 1, we get:
√2x - √3(√3x/√8) = 0
√2x - 3x/√8 = 0
Taking LCM, we get (√2 * √8)x - 3x = 0
4x - 3x = 0
x = 0
Substituting x = 0 in equation 1, we get 0 - √3y = 0
-√3y = 0
Therefore y = 0.
Hence solved. x = 0 and y = 0
Similar questions